Association of Vitamin D with outcome after intra cytoplasmic sperm injection. (2nd January 2017) - Abdullah, Umme Hani; Lalani, Salima; Syed, Fatima; Arif, Sara; Rehman, Rehana
Abstract: Objective : To observe effects of vitamin D levels on pregnancy outcome after intra cytoplasmic sperm injection (ICSI). Method : It was a cross-sectional study conducted in Australian Concept Infertility Medical Center from July 2011 to August 2014. Estimation of 25-hydroxy cholecalciferol (25-OHD) of consented females (252) was done before treatment protocol for ICSI. Results of β hCG performed 14 days after embryo transfer categorized groups; Pregnant with ß hCG more than 25 IU/mL and rest included in non-pregnant group. Both groups were compared by independent sample t -test and Pearson's Chi Square test. Binary Logistic Regression Analysis was used to estimate odds ratio of pregnancy outcome with its predictors including Vitamin D. Results : The mean value of 25-OHD, number of oocytes, fertilized oocytes and endometrial thickness was significantly higher in pregnant women. A significant positive association of 25-OHD with clinical pregnancy and thickness of endometrium was observed. After adjustment with female age and BMI, positive association of vitamin D with endometrial thickness was observed. Conclusion : Deficiency of 25-OHD in females hinders the accomplishment of optimal endometrial thickness required for implantation of embryo after ICSI. The improvement in vitamin D status can thus improve success results in assisted reproductive clinics.